How many skin barriers haveth we: Percutaneous egression of ions?. Issue 2 (9th November 2021) - Chiang, Chavy; Maibach, Howard I.
Abstract: Introduction: Skin provides critical barrier properties that enable terrestrial life. Myriad research has focused on the "water barrier" to transepidermal water loss (TEWL) despite there being a multitude of skin barrier properties. We asked what other barrier properties may have been overlooked and compiled data demonstrating the "electrolyte barrier" to be of potential clinical relevance. Methods: A literature search was conducted through PubMed, Embase, Google Scholar, and Web of Science databases for the following keywords: "transepidermal" or "epidermal" or "cutaneous" or "skin" or "percutaneous" and "ion" or "sodium" or "chloride" or "potassium" or "electrolyte" and "flux" or "egression." Textbooks at the University of California, San Francisco were also hand reviewed. Experimental studies quantifying in vivo or ex vivo percutaneous egression of ions in response to human skin barrier perturbation were included. Results: Experimental damage to skin, mostly by tape‐stripping, frequently induced increased ion flux rates through the epidermis, in addition to increases in TEWL values. Interestingly, barrier perturbation did not always result in a concomitant rise in TEWL and transepidermal ion flux rates, such as in delipidization, indicating a distinction between the two barriers. Conclusion: Quantifying the percutaneous egression of ions in response to physical or chemical alterations may offer additional data that are not to be captured with TEWL studies exclusively. Continued efforts should be made to: (1) advance this technique as a method of assessing skin status and (2) enhance our understanding of other barriers and mechanisms.